Comparisons of design wind pressures on roof-mounted solar arrays between wind tunnel tests and codes and standards. Issue 4 (March 2021) - Wang, Jingxue; Yang, Qingshan; Hui, Yi
The current codes and standards concerning wind loads on roof-mounted solar panels are discussed and summarized. Wind pressures on flat- and slope-roof-mounted solar arrays obtained from wind tunnel tests are compared with the recommended design values in ASCE 7-16 and JIS C 8955: 2017. Different parameters, including building side ratio, aspect ratio and parapet height, are examined. Results show that the largest wind pressures on flat-roof-mounted solar panels of all zones in ASCE 7-16 tend to be 10% to 26% smaller than the experimental results when normalized tributary area An is larger than 10 3 . Uplift wind forces on flat-roof-mounted solar panels in downstream regions obtained from experiments can be larger than the recommended values in JIS C 8955: 2017 for adverse wind, but downward force coefficients are basically smaller than those in JIS C 8955: 2017 for fair wind. 40% to 60% increase on the pressure equalization factor for slope-roof-mounted solar panels is suggested for the potential refinement of ASCE 7-16 based on this study. Meanwhile, proposed pressures of slope-roof-mounted solar panels in JIS C 8955: 2017 might be too conservative according of experimental results.